Induksi Kematangan Gonad Induk Jantan Kerang Abalone (Haliotis asinina) dengan Metode Laserpunktur [Induction Of Gonad Maturity Males Broodstock Abalone Shell (Haliotis asinina) With Laserpunctur Methods ] - Sudarno Sudarno; Rahayu Kusdarwati; Aprilia Putri Astutie (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Abalone is one kind of shellfish fisheries of the world has become a commodity which is currently experiencing increased demand, especially from international markets. As one initial step of a series of required maintenance management process of cultivating a good broodstock, to get the broodstock with the maximum level of gonad maturity is by induction using laserpunctur. Laserpunctur appropriate technology has been shown to accelerate the growth process, increase and accelerate gonadal maturation and spawning shorten the reproductive cycle of some species. The purpose of this study was to determine the effect laserpunctur fired on gonadal organs of the male gonadal maturity of abalone shells and the best energy of the male gonadal maturation affect abalone shells. The treatment used is laserpunctur irradiation on the male gonad organ abalone shells with a energy of 0 Joule (control), 0.5 Joules for 50 seconds, 1 Joule for 100 seconds, 1.5 Joules for 150 seconds and 2 Joule for 200 seconds. Each treatment was repeated four times. The results of this study was the laserpunctur irradiation fired on the gonadal organs influence the development of gonadal maturity of male broodstock abalone shells. The best energy of laserpunctur in the male gonad maturation affects the abalone shells is 1.5 Joules for 150 seconds. The results of histological observation of gonadal male broodstock H. asinina showed varying degrees of gonadal development in the process of gametogenesis is marked with an individual's reproductive cycle.